2015
DOI: 10.1099/vir.0.000211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the functional domain of the porcine epidemic diarrhoea virus receptor

Abstract: Porcine aminopeptidase N (pAPN) is a functional receptor for porcine epidemic diarrhoea virus (PEDV). Although PEDV is known to use the pAPN as the major receptor for cell entry, the crucial domain of the pAPN that interacts with the PEDV is still unknown. In the present study, in order to determine the crucial domain of the pAPN, the extracellular domain of pAPN was divided into three subdomains named SPA, SPB and SPC, based on its secondary structure. Recombinant plasmid pcDNA3.1 expressing SPA, SPB and SPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Such diverse tissue tropisms may be due to different receptor usage and/or proteolytic processing of the S proteins between PEDV and TGEV. For many years, the TGEV receptor, porcine aminopeptidase N (pAPN), was also considered to be the putative receptor of PEDV (40)(41)(42)(43). However, recent studies revealed that PEDV could infect pAPN knockout cell lines (11), but the protease activity of pAPN enhanced PEDV infection (10), suggesting that pAPN is not the cellular receptor for PEDV.…”
Section: Figmentioning
confidence: 99%
“…Such diverse tissue tropisms may be due to different receptor usage and/or proteolytic processing of the S proteins between PEDV and TGEV. For many years, the TGEV receptor, porcine aminopeptidase N (pAPN), was also considered to be the putative receptor of PEDV (40)(41)(42)(43). However, recent studies revealed that PEDV could infect pAPN knockout cell lines (11), but the protease activity of pAPN enhanced PEDV infection (10), suggesting that pAPN is not the cellular receptor for PEDV.…”
Section: Figmentioning
confidence: 99%
“…They also reported the C-terminal ␣domain might be important as the active site. More recently, Shan et al reported the protein structure on pAPN by SWISS-MODEL web server (Shan et al, 2015). They reported pAPN contains small intra-cellular domain and large extra cellular domain divided into 3 subdomains named SPA, SPB and SPC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even new isolates of PEDV are able to show distinct signs of CPE in Vero cells only after several passages (Pan et al, 2010), which could probably be an adaptation period. As the functional domain study on pAPN, Shan et al reported that SPC region on pAPN might be putative functional domain for PEDV infection (Shan et al, 2015). They found MDCK cells expressing only SPC region successfully infected by PEDV and even shown cytopathic effects (CPE).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect immunofluorescence assay was performed to detect the expression of Lfcin on the cell surface of ΔthyA L.casei -LFEC as previously described [ 19 ]. Briefly, 1 mL of ΔthyA L.casei -LFEC cultured in GM17 broth for 12 h was centrifuged, washed with PBS three times, and resuspended in 1 mL of sterile PBS-3% bovine serum albumin (BSA) containing mouse anti-myc antibody; following the incubation at 37°C for 1 h, the cells were harvested, washed three times, and incubated in 1 mL of FITC-conjugated goat anti-mouse IgG antibody (diluted at 1:500) at 37°C for 1 h; then, the cells were washed three times, transferred onto a glass slide, and fixed with cold acetone for 30 min; Confocal microscope was used to observe fluorescence signals.…”
Section: Methodsmentioning
confidence: 99%